Formulasi Sediaan Hair Tonic Ekstrak Rumput Laut (Hormophysa Triquetra) Dengan Kombinasi Ekstrak Kemiri (Aleurites Moluccana) Sebagai Penumbuh Rambut - Puput Putri Hayati; Ginanjar Pratama; Dini Surilayani; Afifah Nurazizatul Hasanah (JURNAL AGROINDUSTRI HALAL, 2024)
Hormophysa triquetra seaweed is one of the marine natural resources that has not been utilized optimally by society. H. triquetra seaweed has a dominant pigment, namely fucoxanthin, which has anti-cancer and anti-obesity properties. Seaweed is widely used as a cosmetic product by utilizing its ingredients. H. triquetra seaweed contains flavonoids, phenols as antioxidants which are able to repair damaged hair cells and produce skin tissue which is conducive to hair growth, besides the vitamin C content which can increase blood circulation and provide nutrition for hair follicles. Aleurites moluccana candlenut oil contains high levels of oleic acid and has activity as a hair growth stimulant which has been widely used for generations as a hair tonic. In addition, the antioxidant properties of candlenut oil's oleic acid are believed to slow hair loss and accelerate hair growth. The aim of this research is to determine the formulation and characteristics of the best hair tonic made from H. triquetra seaweed and candlenut extract as a hair growth agent. A completely randomized design with 4 treatments and 3 replications was used in this experiment. The best results were in the F0 treatment because it showed good physical stability in the test animals and fast hair length growth among other treatments because the samples used contained the highest seaweed extract and contained antioxidants which could protect hair and maintain good hair pigmentation.